A LOFAR census of non-recycled pulsars: Average profiles, dispersion measures, flux densities, and spectra - Bilous, A.; Kondratiev, V.; Kramer, M.; Keane, E.; Hessels, J.; Stappers, B.; Malofeev, V.; Sobey, Charlotte; Breton, R.; Cooper, S.; Falcke, H.; Karastergiou, A.; et al. (EDP Sciences, 2016)
We present first results from a LOFAR census of non-recycled pulsars. The census includes almost all such pulsars known (194 sources) at declinations Dec > 8 and Galactic latitudes jGbj > 3, regardless of their expected flux densities and scattering times. Each pulsar was observed for 20 min in the contiguous frequency range of 110-188 MHz. Full-Stokes data were recorded. We present the dispersion measures, flux densities, and calibrated total intensity profiles for the 158 pulsars detected in the sample. The median uncertainty in census dispersion measures (1:5 × 10-3 pc cm-3) is ten times smaller, on average, than in the ATNF pulsar catalogue. We combined census flux densities with those in the literature and fitted the resulting broadband spectra with single or broken power-law functions. For 48 census pulsars such fits are being published for the first time. Typically, the choice between single and broken power-laws, as well as the location of the spectral break, were highly influenced by the spectral coverage of the available flux density measurements. In particular, the inclusion of measurements below 100MHz appears essential for investigating the lowfrequency turnover in the spectra for most of the census pulsars. For several pulsars, we compared the spectral indices from different works and found the typical spread of values to be within 0.5-1.5, suggesting a prevailing underestimation of spectral index errors in the literature. The census observations yielded some unexpected individual source results, as we describe in the paper. Lastly, we will provide this unique sample of wide-band, low-frequency pulse profiles via the European Pulsar Network Database.